Memory retrieval, reconsolidation, and extinction: Exploring the boundary conditions of post-conditioning cue exposure - Ferrara, Nicole C.; Kwapis, Janine L.; Trask, Sydney (Frontiers in Synaptic Neuroscience, 2023)
Following fear conditioning, behavior can be reduced by giving many CS-alone presentations in a process known as extinction or by presenting a few CS-alone presentations and interfering with subsequent memory reconsolidation. While the two share procedural similarities, both the behavioral outcomes and the neurobiological underpinnings are distinct. Here we review the neural and behavioral mechanisms that produce these separate behavioral reductions, as well as some factors that determine whether or not a retrieval-dependent reconsolidation process or an extinction process will be in effect.